Vitamin D Supplementation is Associated with Attenuated Ocular Surface Oxidative Stress in Mild Thyroid Eye Disease: A Preliminary Interventional Study - Mardijas Efendi; Hendriati; Pattih Primasakti; Yolanda Wulandari Erwen; Rani Apriani (HM Publisher, 2025)
Background: Thyroid eye disease (TED) is an autoimmune orbitopathy where inflammation drives significant oxidative stress, contributing to patient morbidity. Malondialdehyde (MDA), a lipid peroxidation product, is a key biomarker of this oxidative damage. While vitamin D has known systemic immunomodulatory effects, its capacity to mitigate local oxidative stress on the ocular surface in TED is poorly understood. This study aimed to investigate the association between oral vitamin D supplementation and tear film MDA levels in patients with mild TED. Methods: A prospective, single-center, quasi-experimental pre-post study without a control group was conducted on 15 patients diagnosed with mild, active TED (Clinical Activity Score ≤3). Participants received 1000 IU of oral cholecalciferol (Vitamin D3) daily for 21 consecutive days. The primary outcome was the change in tear film MDA concentration, measured by ELISA. Secondary outcomes included serum 25-hydroxyvitamin D [25(OH)D] levels and clinical ocular surface parameters (Ocular Surface Disease Index [OSDI], Tear Break-Up Time [TBUT], Schirmer's I test). Results: A statistically significant reduction in mean tear film MDA levels was observed, decreasing from a baseline of 8.69 ± 4.15 ng/L to 5.70 ± 1.56 ng/L post-intervention (p<0.001). This was accompanied by a significant increase in mean serum 25(OH)D levels from 18.2 ± 5.9 ng/mL to 29.8 ± 6.4 ng/mL (p<0.001). Significant improvements were also noted in OSDI scores (p=0.002) and TBUT (p=0.005). The reduction in tear film MDA showed a significant negative correlation with the increase in serum 25(OH)D (r = -0.68, p=0.005). Conclusion: In this preliminary, uncontrolled study, short-term oral vitamin D supplementation was associated with a significant attenuation of ocular surface oxidative stress in patients with mild TED. These findings provide initial biochemical evidence for the potential localized benefits of vitamin D and support the need for larger, placebo-controlled randomized trials to validate its role as a safe adjunctive therapy for managing the ocular surface component of this disease.